Hybridization and localized flat band in the WSe2/MoSe2 heterobilayer. (22nd January 2023) - Khalil, Lama; Pierucci, Debora; Velez-Fort, Emilio; Avila, José; Vergnaud, Céline; Dudin, Pavel; Oehler, Fabrice; Chaste, Julien; Jamet, Matthieu; Lhuillier, Emmanuel; Pala, Marco; Ouerghi, Abdelkarim
Abstract: Nearly localized moiré flat bands in momentum space, arising at particular twist angles, are the key to achieve correlated effects in transition-metal dichalcogenides. Here, we use angle-resolved photoemission spectroscopy (ARPES) to visualize the presence of a flat band near the Fermi level of van der Waals WSe2 /MoSe2 heterobilayer grown by molecular beam epitaxy. This flat band is localized near the Fermi level and has a width of several hundred meVs. By combining ARPES measurements with density functional theory calculations, we confirm the coexistence of different domains, namely the reference 2H stacking without layer misorientation and regions with arbitrary twist angles. For the 2H-stacked heterobilayer, our ARPES results show strong interlayer hybridization effects, further confirmed by complementary micro- Raman spectroscopy measurements. The spin-splitting of the valence band at K is determined to be 470 meV. The valence band maximum (VBM) position of the heterobilayer is located at the Γ point. The energy difference between the VBM at Γ and the K point is of −60 meV, which is a stark difference compared to individual single monolayer WSe2 and monolayer WSe2, showing both a VBM at K .